Boustras, Georgios - (:unkn) unknown (My University, 2026)
George Boustras, BEng(Hons), MSc, PhD, CSci, MIChemE, MIFE George is currently Professor in Risk Assessment at European University Cyprus, Dean of the Ioannis Gregoriou School of Business Administration. George is the Director of the Centre for Risk, Safety and the Environment (CERISE). George is a PhD in Probabilistic Fire Risk Assessment from CFES at Kingston University London. George had been appointed as Honorary Research Fellow at CPSE at Imperial College London, and he was KTP Research Fellow at FSEG at the University of Greenwich. He is a Member in a number of professional Organizations (IChemE, IFireE, TEE, ETEK) and a Chartered Scientist at IChemE. He sits at the Management Committee of Secure Societies - Protecting Freedom and security of Europe and its citizens of “HORIZON 2020”. Until recently he was a Member of the Academic Committee of ERNCIP – the European Research Network of Critical Infrastructure Protection at JRC Ispra and the Socio-Economic Committee (SEAC) of the European Chemicals Agency (ECHA). He has consulted private organisations and the Cypriot Government in various occasions. In the past he was a Technical Consultant for the Ministry of Defence of the Republic of Cyprus in carrying out the Risk Assessment of Unexploded Ordnance as part of Gas Exploration. He has been appointed by the President of the Republic as Vice President in the Council of Energy Strategy. He has been appointed by the Ministerial Council of the Republic of Cyprus to Head a Special Task Force that proposeD a new management procedure for the State’s first responders. George is Editor-in-Chief of Safety Science (Elsevier) and Member of the Editorial Board of Fire Technology (Springer), the International Journal of Emergency Management and International Journal of Critical Infrastructure (both Inderscience). George currently supervises 6 PhD students (4 as main supervisor and 2 as co-supervisor).